The effects of exercise on COVID-19 therapeutics: A protocol for systematic review and meta-analysis. Issue 38 (18th September 2020) - Xu, Zhangmeng; Chen, Yong; Yu, Duoduo; Mao, Dongdong; Wang, Ting; Feng, Donghong; Li, Tao; Yan, Shengsong; Yu, Yaming
Abstract: Background: At the end of 2019, peoples normal lives were disrupted by a sudden plague (COVID-19), the huge impact of COVID-19 on society has never been appeared. How to effectively prevent and treat COVID-19 is a concern for all health care workers. Exercise as a green and cheap complementary therapy, which has been proven to improve the immune capacity of the body and prevent infection. The main purpose of this study is to provide a reliable methodological guidance and credible evidence for exercise on COVID-19 therapeutic. Methods: This protocol is guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols. We will search the following database sources for the Randomized controlled trials: the Cochrane Library, PubMed, EMBASE, Web of Science, Chinese Biomedical Literature Database (CBM), Chinese National Knowledge Infrastructure Database (CNKI), Chinese Science and the Wanfang Database. All randomized controlled trials of exercise therapy for COVID-19 in the above database will be considered for inclusion, and high-quality articles will be screened for data extraction and analysis, to summarize the therapeutic effect of exercise on COVID-19 patients. Results: In this study, we hope to find strong evidence for the treatment of COVID-19 by exercise. Conclusion: The conclusion of our study will provide credible evidence to judge whether exercise is an effective intervention on the COVID-19 patients therapeutic, and guide future researches. PROSPERO registration number: CRD42020200883.